Usage of Organic Compounds and Nanoparticles in Everyday Life - Nawaz, Allah; Abdullah, Muhammad; Anwer, Tahseen; Yousaf, Nouman Ahmed; Sarfraz, Rubab; Ahmad, Muhammad Talha; Bindia; Assad, Muhammad Ali; Sajjad, Sadaf; Abbas, Aamir (Indus Journal of Bioscience Research, 2025)
Combining organic molecules and nanoparticles constitutes a pivotal study domain with substantial ramifications in the healthcare, energy, and environmental sustainability sectors. These materials are essential because of their distinctive qualities, such as the molecular adaptability of organic compounds and the nanoscale benefits of nanoparticles, facilitating advanced applications in medicine delivery, pollution reduction, and the creation of innovative materials. This review examines contemporary literature to offer a thorough grasp of their applications, emphasizing their synergistic potential and identifying significant gaps in their development and implementation. The results underscore significant developments in utilizing these materials, accentuating their roles in sustainable energy systems, cutting-edge medical technology, and eco-friendly industrial practices. Furthermore, the review highlights substantial deficiencies, including the inadequate comprehension of their prolonged environmental effects and the difficulties associated with expanding green synthesis techniques. The review identifies gaps and provides practical solutions and future research paths to improve the safe and effective utilization of organic chemicals and nanoparticles. It emphasizes the significance of interdisciplinary collaboration and the creation of strong regulatory frameworks to realize their full potential while maintaining sustainability and ethical accountability. The insights provided establish a significant basis for researchers, governments, and enterprises to utilize these materials for societal progress.